Innovation and Firm Competitiveness as Intervening Variables in Improving Financial Performance of MSMEs - Soesetio, Yuli; Soetjipto, Budi Eko; Handayati, Puji; Winarno, Agung; Rudiningtyas, Dyah Arini; Mawardi, Moh. Cholid; Realita, Tasnim Nikmatullah (Universitas Brawijaya, Indonesia, 2024)
Micro, small, and medium enterprises (MSMEs), especially those operating in the craft industry, often remain overlooked and receive minimal attention from researchers and policymakers even though they have an important role in increasing exports and employment in Indonesia. Nevertheless, craft MSMEs face significant challenges in maximizing innovation and enhancing competitiveness to improve financial performance. Hence, this study aims to investigate how innovation and firm competitiveness influence the financial performance of craft MSMEs. This study utilizes the SEM AMOS analysis tool with data from 403 business actors across three craft centers in West Java: Tasikmalaya, Majelengka, and Bandung. The findings reveal that product, process, and green innovation significantly influence and partially mediate the connection between entrepreneurial orientation and competitiveness. Competitiveness completely mediates the influence of product and green innovation on craft MSMEs' financial performance. Meanwhile, process innovation significantly impacts financial performance both directly and indirectly, emphasizing its importance in enhancing competitiveness and financial outcomes. Continuous improvement and innovation are crucial for boosting competitiveness and financial performance.